(untitled) (Jurnal Arsitektur ARCADE, 2026)
Passive cooling is a critical strategy for reducing energy consumption in buildings located in hot–humid tropical climates, where cooling demand is strongly influenced by both solar heat gains and internal loads from artificial lighting. While daylight-oriented façade design is widely studied for visual comfort, its contribution to reducing lighting-related internal heat gains remains insufficiently explored. This study investigates the relationship between daylight illuminance and internal heat gains from artificial lighting through a simulation-based assessment of a representative tropical room model. Using DIALux, a single office-like space (4 m × 5 m) was simulated under 24 façade configurations derived from variations in window-to-wall ratio (20%, 40%, and 60%), façade orientation (north, south, east, and west), and shading condition (shaded and unshaded). Daylight simulations were conducted on 21 March and 21 June between 08:00 and 16:00. Illuminance results were compared against a 500 lux task-plane threshold to determine the number of lamps required, which was then used as an indicator of lighting energy use and associated internal heat gains. The results show that small openings (20% WWR) consistently require the highest artificial lighting across all orientations. Larger openings do not automatically guarantee daylight sufficiency, particularly for east- and west-facing façades after midday. Shading was found to reduce excessive solar exposure but, in some cases, increased lighting demand due to uneven daylight distribution. Overall, north- and south-facing façades demonstrated superior performance. The study concludes that integrating daylight illuminance analysis with lighting-related heat gain assessment provides a practical framework for linking visual performance and passive cooling strategies in tropical architecture.